Gambaran Kadar Hemoglobin Sebagai Penanda Awal Anemia pada Pegawai Politeknik Unggulan Kalimantan Tahun 2025: Description of Hemoglobin Levels as an Early Indicator of Anemia Among Employees of the Politeknik Unggulan Kalimantan in 2025 - Nahlida Rahmah; Nanda Yaultsa (Politeknik Unggulan Kalimantan, 2025)
Anaemia is a health problem that can reduce employee productivity and work quality. This condition is distinguished by insufficient haemoglobin concentration, which diminishes the blood's ability to carry oxygen. This study aims to determine haemoglobin levels as an early marker of anaemia among employees at the Politeknik Unggulan Kalimantan in 2025. This research utilized a descriptive strategy along with a cross-sectional method, comprising 27 staff members recruited via purposive sampling dependent on the criteria of readiness to be respondents. Haemoglobin levels were measured using a Fortace Haematology Analyser with a normal range of 12.0–16.0 g/dL. The findings demonstrated that the prevalence of anaemia was elevated in females compared to males, with 9 female respondents (33.33%) having low haemoglobin levels, while all male respondents had haemoglobin levels within the normal range. This study highlights the need for regular health monitoring of employees, especially women, as well as the importance of education on nutritious diets and healthy lifestyles to prevent anaemia. The conclusions drawn from this research may serve as the foundation for planning occupational health improvement programmes at the Politeknik Unggulan Kalimantan